Aproximación a un plan de negocios para la exportación de uchuva colombiana a Canadá (2020)
In recent years, no export opportunities have been taken for different fruits and important spaces have been lost in the national market where consumption of national and imported fruits and vegetables has been changed. Since the 80s when it was proposed to diversify exports of non-traditional products. From this moment the Cape Gooseberry positioned itself as a leading product in Colombia's exports. In the course of the specialization, knowledge has been acquired regarding foreign trade (exports and imports), in addition they gave us development tools that seek to establish and create a business opportunity which is the purpose of this project, to establish a business idea feasible for the realization of this in addition to the creation of a cape gooseberry exporting company. The Colombian gooseberry exporting plan in Canada will take advantage of the fact that this fruit is affected as exotic, apart from its benefits it is attractive to the foreign market. On the other hand, it considers an innovative project since it promotes the development of the beneficiary field to the producers. In this degree work, studies are carried out to demonstrate and analyze the viability of the project in terms of marketing, logistics and finance. The studies finally yielded positive results and finally the export of Colombian Cape Gooseberry to Canada will be taken as a great business opportunity.